Empowering Floating Net Cage Fish Farmers Through Educational Strategies in Bohe Silian Village, Berau, East Kalimantan - Santosa, Irfan; Farid, Ahmad; Rusnoto, Rusnoto; Siswiyanti, Siswiyanti; Laga, Surya; Sunardi, Sunardi (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2026)
Cantang grouper (Epinephelus fuscoguttatus × Epinephelus lanceolatus) is a high-value aquaculture commodity in Indonesia. However, small-scale farmers in remote areas such as Bohe Silian Village, Berau, frequently suffer significant economic losses due to high fish mortality rates caused by poor health management and fluctuating water quality. This study aims to evaluate the effectiveness of a strategic educational intervention in enhancing farmers' technical capacity for fish health management in floating net cages (Keramba Jaring Apung/ KJA). A participatory community empowerment approach was employed, combining theoretical socialization, on-site demonstrations, and intensive mentoring. The results program significantly improved farmers' multidimensional knowledge and technical skills in water quality and disease management, with success rates of 79%, 97%, 79%, and 80%, across technical, ecological, economic, and social aspects, respectively. Ultimately, the initiative demonstrated that participatory education strategies effectively strengthen the resilience of small-scale aquaculture in remote coastal areas.